Idiopathic Sudden Sensorineural Hearing Loss in Different Ages: Prognosis of Patients With Initial Total Hearing Loss - Xiong, Wenping; Dai, Qinglei; Wang, Yingjun; Hou, Zhiqiang; Lu, Kunpeng; Sun, Xiao; Duan, Fujia; Wang, Haibo; Zhang, Daogong; Wang, Mingming (Frontiers in Psychology, 2022)
Objective This study aimed to analyze the hearing improvement and prognosis factors of idiopathic sudden sensorineural hearing loss (ISSNHL) in different ages with initial total hearing loss. Methods We reviewed the medical records of 5,711 hospitalized patients with ISSNHL from 2016 to 2021 in our center. All of the patients had been treated with uniform combination drug therapy. After excluding the patients with initial partial hearing loss and those diagnosed with clear etiology, 188 patients were enrolled in this study and divided into six age groups (18–30, 31–40, 41–50, 51–60, 61–70, ≥ 71 years). In all groups, decreases in pure-tone average (PTA) 1 month posttreatment, effective rate, and clinical characteristics (vertigo, tinnitus, hospital stay, comorbidity, and inner ear magnetic resonance imaging) were analyzed. Results Among the 188 enrolled patients, 86% had vertigo. Complete recovery was seen in 0.5% of patients, and marked recovery was seen in 43% of patients. The mean 1 month posttreatment PTAs were as follows: 18–30 years: 80 ± 7.5 dB; 31–40 years: 100 ± 9.0 dB; 41–50 years: 99 ± 8.3 dB; 51–60 years: 101 ± 8.6 dB; 61–70 years: 96 ± 9.6 dB; and ≥ 71 years: 88 ± 13.0 dB. Compared with the other groups, the 18–30- years group showed better recovery of hearing threshold in five frequencies (0.25, 0.5, 1, 2, and 4 kHz, respectively, at octave or semioctave frequencies under air conduction), and the recovery of hearing threshold at 0.25 and 0.5 Hz was better than the recovery at 1, 2, and 4 kHz. According to the results of the chi-square test statistical analysis, vertigo and comorbidities were associated with a poor prognosis of ISSNHL. Conclusion In summary, the treatment outcomes of patients with ISSNHL with initial total hearing loss were poor. There was a significant age-related difference with respect to marked recovery 1 month posttreatment, and the 18–30- years group showed better recovery than the other age groups.